Bioactive solids obtained from montmorillonite functionalization by biogenic compounds to be used as antimicrobial filler - López, Guillermo Pablo (2024)
The growth of fungi and bacteria on material surfaces negatively impacts human health and produces economic losses, and harmful waste for the environment. In the present research, new eco-friendly and low-cost antimi crobial fillers are actively sought by the functionalization of montmorillonite using biogenic compounds. The synthesized hybrids from montmorillonite, natural surfactant, and geraniol were characterized and showed effective antifungal and antibacterial activity.